Anurans from the Lower Cretaceous Jehol Group of western Liaoning, China. - Liping Dong (Public Library of Science (PLoS), 2013)
Background To date, the Lower Cretaceous Jehol Group of western Liaoning, China has yielded five monotypic genera of anurans, including Liaobatrachus grabaui, Callobatrachus sanyanensis, Mesophryne beipiaoensis, Dalianbatrachus mengi, and Yizhoubatrachus macilentus. However, the validity and distinctness of these taxa have been questioned. Methodology/principal finding We provide a comprehensive analysis of the Jehol frogs that includes a re-examination of the published taxa as well as an examination of a number of new specimens that have been collected over the past 10 years. The results show that the five previously named taxa can be referred to three species of one genus-Liaobatrachus grabaui, L. beipiaoensis comb. nov. and L. macilentus comb. nov.. The diagnosis of Liaobatrachus is revised, and a new diagnosis is provided for each species of this genus. We also establish Liaobatrachus zhaoi sp. nov., on the basis of a dozen well-preserved specimens from a new locality. This taxon is distinguished by a unique combination of characteristics, including relatively long hind limbs, a rounded rather than triangular acetabulum, and a gradually-tapering cultriform process of the parasphenoid. In addition, an unnamed frog from a higher horizon, which has narrow sacral diapophyses and particularly long legs, is different from Liaobatrachus and represents another form of anuran in the Jehol Biota. Conclusion/significance Comparisons with other Mesozoic and extant anurans and the primary phylogenetic analysis both suggest that Liaobatrachus is a member of the anuran crown-group and forms a polytomy with leiopelmatids (Ascaphus and Leiopelma) and the remaining crown-group anurans (Lalagobatrachia).